Маяковский – новатор языка? Словообразовательная структура неологизмов Маяковского и их роль в современном русском языке - Jana Kitzlerova (Studia Rossica Posnaniensia)
This paper deals with the word-formation of Mayakovsky’s neologisms, the principles of their composition and also the objects subjected to neologization. Attention is also paid to the Nachleben of these neologisms in contemporary Russian, based on the research into the Russian National Corpus. The paper is a result of the analysis of all Mayakovsky’s neologisms listed in A. Humesky’s book Majakovskij and His Neologisms (1964), except for those originated by the simple connection of two words or word components. The results were compared with the most recent work dealing with Mayakovsky’s neologisms, V. N. Valavin’s dictionary (Word-formation of Mayakovsky. An Attempt at a Dictionary of Occasiоnalisms). It is argued that the main word-formation principle is that of composition (substantives and adjectives) and suffixation (verbs), that even today many neologisms show surprising vitality, and also that not all of the neologisms ascribed to Mayakovsky are indeed his authorial creations.